Evaluasi Potensi dan Model Pengembangan Bisnis Magic Water pada Industri Minuman Sehat di Era Gaya Hidup Modern - Bayuadi Bayuadi; M. Afrizal Miradji; Lizaristi Berliana Putri; Muhammad Rizky Rizal Maulana; Nurul Fitrianingtyas; Icha Nurul Laili Fitriah; Muhammad Arfian Bayu Nugroho (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study aims to evaluate the potential and business development model of Magic Water as part of the growing healthy beverage industry, in line with increasing public awareness of a more health-oriented modern lifestyle. The study was conducted through market data analysis from official international reports, literature studies, and a review of relevant natural beverage product development strategies. The results of the study show that global demand for functional and health drinks is experiencing stable growth, as reflected in market value projections for 2030 and 2033. These findings show that innovation based on natural ingredients, branding power, and digital marketing strategies are key determinants in increasing the competitiveness of Magic Water products in domestic and international markets. This research emphasizes the importance of integrating product uniqueness, health trends, and sustainable business approaches to ensure Magic Water can secure a strategic position and grow competitively amid the increasingly progressive dynamics of the global healthy beverage industry.